Antibiotic sensitivity pattern in culture positive typhoid fever cases isolated at Patan hospital - Sanjay Kumar Shrestha; Shova Basnet (Association of Clinical Pathologists of Nepal, 2019)
Background: Enteric fever is one of the most common systemic infections of developing countries like Nepal. The changing trend of antibiotic susceptibility and increasing rate of resistance to the commonly used antibiotics has been of great concern in the proper treatment and prevention of this disease. This study aims to investigate the current antibiotic susceptibility pattern of Salmonella typhi and paratyphi A and B. Materials and Methods: This study was carried out at Patan hospital of Lalitpur, Nepal from ____ to -------. Blood culture sample were collected from suspected patients presenting to different departments of the hospital and tested microbiologically by standard procedure. Antibiotic susceptibility test was performed by Kirby Bauer Disc Diffusion method and results were interpreted by National Committee for Clinical Laboratory (NCCLS) guidelines. Results: Out of the total sample of 212, 40(18.8%) cases were isolated as Salmonella species. Out of these, 29(72.5%) cases were S typhi and 11(27.5%) were S paratyphi. Isolates were mainly from adult age group. Regarding the antibiotic susceptibility pattern, the sensitivity to chloramphenicol was 95% and to cotrimoxazole 97% whereas the sensitivity to ciprofloxacin was 52.5% and 27.5% for Ofloxacin. Nalidixic Acid Resistance Salmonella typhi strain was 60.0 percent. Sensitivity to ceftriaxone, meropenem and colistin was found to be 100 percent. Conclusions: A high degree of variability is seen in antimicrobial sensitivity pattern with very high degree of sensitivity to the historically used antibiotics like chloramphenicol and cotrimoxazole. Unfortunately, sensitivity to quinolones was seen to be very low, which were used widely in the last two decades.